Experimental Design Sensory Quality Boba Developed From Pumpkin - Juliana Juliana; Rudy Pramono; I Gusti Anom Yudistira; Grace Kezia Josephine; Jessica Shaina Wijaya (International Journal of Applied Business and International Management, 2022)
In this day and age, boba topping is one of the most popular toppings for selling drinks, especially bubble tea. The boba itself was discovered in 1987 in Taiwan but has only recently become popular. Researchers want to make innovations from boba by adding pumpkin as the main ingredient of boba. Pumpkin has many benefits, so it is excellent and safe to use as a topping. In this study, researchers wanted to know about the original boba's color, taste, texture, and aroma, which would change if the essential pumpkin ingredient was added. This research is experimental. The researcher used an organoleptic test consisting of a hedonic test and a hedonic quality test to determine the panelists' preferences and good and bad impressions of the boba made. The researcher distributed the product to 20 trained panelists to be given an assessment. The results showed that the comparison of preferences between authentic boba and boba using pumpkin as the primary ingredient was not much different. The products made are still favored by the panelists. There are also some significant changes to the boba in color, taste, texture, and aroma.